2019
DOI: 10.1016/j.proci.2018.07.036
|View full text |Cite
|
Sign up to set email alerts
|

The role of flow interaction in flame–flame interaction events in a dual burner experiment

Abstract: A dual burner experiment is used to investigate how flow interactions affect local flame-flame interaction in turbulent premixed flames. The presence of adjacent flows influences the local structure of these flames and understanding the sensitivity of these flames to adjacent flows is essential for multinozzle combustion devices. To study this sensitivity, a high-aspect-ratio Bunsen flame operating at a constant flow velocity is placed adjacent to an identical burner with non-reacting flow at varying velocitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They suggested that the maximum flame length decreases as the number of slits increases, and the shear layer between flames can cause flame surface distortion due to vortex action. Tyagi et al [20] conducted an experimental study of local flame-fire interaction in turbulent premixed flames. They suggested that when there is high shear flow between adjacent flames, a local interaction occurs in which the flame structure bends toward the flame center.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the maximum flame length decreases as the number of slits increases, and the shear layer between flames can cause flame surface distortion due to vortex action. Tyagi et al [20] conducted an experimental study of local flame-fire interaction in turbulent premixed flames. They suggested that when there is high shear flow between adjacent flames, a local interaction occurs in which the flame structure bends toward the flame center.…”
Section: Introductionmentioning
confidence: 99%
“…This coupling is particularly prominent under lean fuel conditions, where the flame is close to its extinction limit, making it more susceptible to inlet disturbances. From the perspective of interaction processes, the interaction between the flame and the vortex behind the flame stabilizer [3,4], inter-flame collisions [5], and the interaction between the flame and sound waves [6,7] all have a significant impact on the stability of a combustion system. Extensive experimental and numerical simulation studies [8][9][10][11] have been conducted by researchers both domestically and internationally, aiming to deepen the understanding of sound wave and heat release behavior from the perspective of physical coupling mechanisms.…”
Section: Introductionmentioning
confidence: 99%